2021
DOI: 10.3389/fmed.2021.715213
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Changes in Bloodstream Infection With Acinetobacter Baumannii Complex in Intensive Care Units in Eastern China: A Retrospective Cohort Study

Abstract: Background: There is little evidence on the changing prevalence, microbiological profile, and outcome of nosocomial Acinetobacter baumannii complex (ABC)-caused bloodstream infection (ABCBSI) specified in intensive care units (ICUs) in long-term studies, especially in China.Objective: We aimed to investigate changes in incidence, antibiotic resistance, therapy, and prognosis of ABCBSI in ICUs in eastern China during 2009–2018.Methods: A multicenter retrospective cohort study was conducted, and microbiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…21 A recent study revealed that the frequency of ABC bacteremia increased significantly in the ICUs in eastern China during 2009-2018, as did the resistance rate to carbapenem. 15 In this study, the resistance rate to imipenem was 95.7% in year 2017-2018, which is higher than in the CHINET data. We analyzed the clinical data of patients with ABC bacteremia during the past 12 years.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…21 A recent study revealed that the frequency of ABC bacteremia increased significantly in the ICUs in eastern China during 2009-2018, as did the resistance rate to carbapenem. 15 In this study, the resistance rate to imipenem was 95.7% in year 2017-2018, which is higher than in the CHINET data. We analyzed the clinical data of patients with ABC bacteremia during the past 12 years.…”
Section: Discussioncontrasting
confidence: 61%
“…A recent retrospective cohort study of Chinese ICUs found that the incidence of ABC bacteremia and prevalence of antibiotic resistance increased markedly during the past decade, along with increasing pneumonia-related infections and worrisome mortality. 15 Therefore, we performed this single-center retrospective study to explore differences in clinical profile and prognosis between patients with pneumonia-and non-pneumonia-related ABC bacteremia, and identified possible independent risk factors for 30-day mortality.…”
Section: Introductionmentioning
confidence: 99%
“…What turned A. baumannii into an urgent threat is resistance to multiple antibiotics, especially carbapenems (Ramirez et al 2020), and the resistance mechanisms that A. baumannii has achieved consist of β-lactamases, aminoglycoside-modifying enzymes, permeability defects, e ux pumps, and target site modi cations (Kyriakidis et al 2021; Lee et al 2017). The infection of A. baumannii has caused great damage to public health worldwide, and the prevalence of infection could be 2%-4% among all medical-related infections and over 10% in the ICU (Lotsch et al 2020;Ma and McClean 2021;Meng et al 2021). A total of 1011 strains collected from 48 countries show that more than half of the strains are multidrug-resistant (MDR) (Lob et al 2016); unfortunately, it is estimated that the mortality of MDR baumannii is more than 50% (Ma and McClean 2021).…”
Section: Introductionmentioning
confidence: 99%
“…strains increased by 2.7-fold in 2018 compared with 2012 ( 23 , 24 ). Previously, we reported a marked increase in the incidence of A. baumannii– related bloodstream infections and incidence of pneumonia-related A. baumannii infections in ICUs in China that were 3.2-fold higher during 2017–2018 than during 2011–2012 ( 25 ). A. baumannii was the most frequent bacterial isolate in ventilator-associated pneumonia in China, and rates were 35.7%–52.7% ( 26 , 27 ).…”
mentioning
confidence: 97%
“…According to CHINET reports, carbapenem-resistant A. baumannii strains increased from 31% in 2005 to 66.7% in 2014 ( 28 ), then to ≈80% in 2018 ( 29 ). We previously reported that carbapenem resistance rates in ICUs in China increased from 25% during 2011–2012 to 95.7% during 2017–2018 ( 25 ). A multicenter study of ICUs in China reported that multidrug-resistant (MDR) A. baumannii was detected in 40% of all cases ( 30 ).…”
mentioning
confidence: 99%